Birokrasi Pemerintahan Pendekatan Sistem Hukum Moral dan Manajemen dalam Upaya Pencegahan Korupsi di Indonesia - Saepudin, Eli Apud; Laksana, April; Wahyiah, Ita Rosita (FIA Unkris Press, 2023)
The bureaucracy has full authority in the management of government budgets and the delivery of public services. Bureaucratic power can lead to abuse of power and corruption in government activities. Lord Epton sad